Engineering Rhynchostylis retusa-like heterostructured α-nickel molybdate with enhanced redox properties for high-performance rechargeable asymmetric supercapacitors. Issue 47 (20th November 2019) - Rama Raju, Ganji Seeta; Pavitra, Eluri; Nagaraju, Goli; Chodankar, Nilesh R.; Vishwanath, Sujaya Kumar; Park, Jin Young; Huh, Yun Suk; Han, Young-Kyu
Abstract : Rhynchostylis retusa -like α-NiMoO4 was synthesized using a simple, single-step, and cost-effective wet-chemistry approach, and it exhibited the superior electrochemical properties. Abstract : The demand for battery-type materials having hierarchical architectures, large surface areas, and excellent redox properties, to develop high energy density asymmetric supercapacitors (ASCs), is increasing. Herein, a facile single-step wet chemical method is proposed, which allows an engineered combination of α-NiMoO4 hierarchical heterostructures to be used as advanced battery-type electrodes for ASCs. The as-synthesized architectures consist of versatile nanogeometries including nanowires, nanosheets, and nanoparticles in the form of Rhynchostylis retusa -like heterostructures, which synergistically enhance the energy storage properties; specifically, at a current density of 2 A g −1, heterostructured α-NiMoO4 exhibits a superior specific capacitance of 1061 F g −1 and an outstanding cycling stability of 96%. Moreover, an aqueous ASC is fabricated by combining such a redox-type α-NiMoO4 heterostructure and activated porous carbon as the positive and negative electrodes, respectively, separated with a piece of filter paper. This device shows high energy and power densities (31.8 W h kg −1 and 786.5 W kg −1, respectively), which are useful to operate various portable electronic appliances. Together with the excellent cycling stability and energy storage properties, the synthesized heterostructured metal molybdates exemplify a new approach to develop novel electrode materials for high-performance aqueous ASCs.